Advances in characterization of black carbon particles and their associated coatings using the soot-particle aerosol mass spectrometer in Singapore, a complex city environment - M. Ma; M. Ma; L.-H. Rivellini; Y. Zong; Y. Zong; M. Kraft; M. Kraft; L. E. Yu; L. E. Yu; A. K. Y. Lee (Atmospheric Chemistry and Physics)
Atmospheric black carbon can act as a short-lived climate forcer and carrier of toxic compounds. This work aims to utilize aerosol compositions detected by a soot-particle aerosol mass spectrometer to advance our understanding of the emission and atmospheric processing of refractory BC (rBC) in Singapore. Positive matrix factorization (PMF) analysis of rBC and organic aerosols (OAs) (PMFbase) identified two traffic factors with differences in rBC content, coating thickness, and diurnal pattern, which could potentially help differentiate gasoline and diesel vehicular emissions. Additionally, two secondary OA (SOA) factors influenced by local chemistry and/or regional transport (less-oxidized oxygenated OA (LO-OOA) and more-oxidized OA (MO-OOA)) were identified. Including metals in the PMF (PMFmetal) improved the quality of source apportionment significantly. An industrial- and shipping-influenced OA separated from traffic emissions was strongly associated with heavy metals (e.g., V+ and Ni+) that might pose higher potential risks to human health. Two biomass burning OA (BBOA) factors with different degrees of oxygenation were also identified. Although the aged BBOA component was highly oxidized, its strong association with K3SO<msubsup>4-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="339da67f118260d512683cde4508e1ea"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-8185-2025-ie00001.svg" width="9pt" height="16pt" src="acp-25-8185-2025-ie00001.png"/></svg:svg> distinguished it from other background MO-OOAs, which generally lacked distinctive OA signatures. Integration of both metals and inorganic aerosols (IAs) into the PMF (PMFall) further identified an additional aged BBOA component that was associated with nighttime IAs and organo-nitrate formation. Furthermore, PMFall revealed concurrent LO-OOA and nitrate formation during daytime, whereas photochemical production of MO-OOAs was linked to acidic sulfate formation, indicating the importance of investigating the interaction between SOA and IA formation and their mixing state in complex city environments.